(untitled) (International Journal of Environmental Sciences, 2025)
Osmo-convective dehydration is one of the combo-drying techniques for shelf stable dehydrated products. Usually dried carrots are used in soups, curries, pastries, sauces and other types of ready-made meals. But for direct consumption of osmo-dehydrated products, it is pre-requisite to have desirable mass transfer and sensory properties of final products. Pre-treatmentsplay an important role to enhance mass transfer and maintain sensory quality. Hence the present investigation was carried out to assess the effect of freeze-thaw pre-treatment on quality of osmo-convectively dehydrated carrot slices. Steam blanched carrot slices were frozen and thawed at different freezing and thawing temperature before osmo-convective dehydration. The effect of freezing and thawing temperature on mass transfer kinetics after osmosis and colour, texture (hardness), apparent density, shrinkage ratio, loss of shrinkage and sensory parameters after convective drying of osmosed carrot slices were evaluated. Sugar gain and water loss of pre-treated carrot slices increased with an increase in freezing and thawing temperature. Freezing and thawing treatment caused a significant reduction in hardness of final product. Lower freezing and thawing temperature resulted in higher percentage of shrinkage ratio as comparative to higher temperature of freezing and thawing. Lowest apparent density (1.211 g/ml) was recorded for the osmo-convectively dehydrated carrot slices prepared at lower freezing and thawing temperature. Osmo-convectively dehydrated carrot slices prepared by using -25o C freezing and 5o C thawing temperature resulted in desirable mass transfer, retention of hardness, lower loss of shrinkage (%) and highest score for all sensory parameters.